ORAL HEALTH RELATED KNOWLEDGE, BEHAVIOR AND QUALITY OF LIFE DIFFERENCES BETWEEN ADOLESCENTS FROM PESANTREN AND NON PESANTREN - Fatimah, Siti; Amalia, Rosa; Priyono, Bambang (Odonto : Dental Journal, 2021)
Background: Adolescents from Islamic boarding school adopted simpler life than those not from Islamic boarding school. It can be a trigger of knowledge, behavioural, and oral diseases differences. Neglecting oral diseases will affect the quality daily lives. The aim of this study is to know the differences of oral health related knowledge, behaviour, and quality of life between adolescents from Pesantren and non Pesantren. Method: This study was observational with a cross-sectional design. The study was conducted on 242 adolescents at Madrasah Aliyah Pesantren and non Pesantren in Banjarmasin City, South Kalimantan. The data of research variables were obtained through online questionnaires. Result: Statistical analysis indicated there were no significant differences of oral health knowledge (p=0,727>0,05) and quality of life (p=0,711>0,05), but there was significant difference of oral health behavior (p=0,038<0,05) between adolescents from Pesantren and non Pesantren. Adolescents from Pesantren have lower oral health behaviour when compared to adolescents from non Pesantren.Conclusion: The oral health knowledge and quality of life possessed by adolescents from Pesantren were not different from those not from Pesantren. Oral health behavior of adolescents from Pesantren was different than adolescents from non Pesantren. It still needs to be improved.